167k views
0 votes
Rearrange the formula for V1 get the formula for V1

Rearrange the formula for V1 get the formula for V1-example-1
User Sanj
by
6.1k points

1 Answer

4 votes

To isolate v₁ from the given equation, subtract aΔt from both members of the equation and simplify:


\begin{gathered} v_2=v_1+a\cdot\Delta t \\ \Rightarrow v_2-a\cdot\Delta t=v_1+a\cdot\Delta t-a\cdot\Delta t \\ \Rightarrow v_2-a\cdot\Delta t=v_1 \\ \therefore v_1=v_2-a\cdot\Delta t \end{gathered}

Therefore, the formula for v₁ is:


v_1=v_2-a\cdot\Delta t

User Semnodime
by
4.5k points